The influence of the block angle on swimming sprint starts - Elliott, G. M.; Sinclair, H. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
The use of the swimming startin9 blocks is a relatively recent occurance and even in the 1950's the instruction on racing start in some text books referred to standing starts from the edge of the pool deck. In the Mexico Olympics, the swimmers were allowed to use a sloping angle of 15° maximum. During the FINA Meetings in Mexico, it was agreed thatthe maximum angle of starting blocks should be 10°. It would seem probable that this ruling was changed because of the difficulty many swimmers had in maintaining their balance on a 15° angle sloping platform. There is however no apparent indication of the value of sloped blocks to the actual start. If one hypothesises that the direction of ground reaction is not necessarily dependent on the slope of the ground but rather on the size of the frictional forces developed, then it could be said that the slope of the blocks is incidental to good starting form.